Prevalence of Extended-Spectrum Beta-Lactamase (ESBL)–Producing Escherichia coli in Humans, Food, and Environment in Kathmandu, Nepal: Findings From ESBL E. coli Tricycle Project - Jyoti Acharya; Runa Jha; Tulsi Ram Gompo; Sharmila Chapagain; Lilee Shrestha; Nisha Rijal; Anjana Shrestha; Pragya Koirala; Suraj Subedi; Binita Tamang; Hari Prasad Kattel; Bishal Khaniya; et al. (International Journal of Microbiology)
The need to address antimicrobial resistance (AMR) through a One Health (OH) approach is now well recognized. There is, however, limited guidance on how AMR surveillance should be implemented across sectors to generate meaningful AMR and AMU data for decision-making. Using a sympatric approach to cross-sector sample collection, Nepal adopted the WHO extended-spectrum beta-lactamase (ESBL)–producing Escherichia coli (E. coli) Tricycle Project as a step toward OH surveillance for assessing the prevalence of ESBL-producing E. coli across human, veterinary, and environment sectors. This involved a three-stage approach: identification of human hotspots (Stage 1) and sample collection sites for poultry (Stage 2) and wastewater (Stage 3). A total of 53 blood cultures from patients with bloodstream infections (BSIs), 100 stool samples from healthy pregnant women, 220 poultry ceca from slaughterhouses and live markets, and 48 wastewater samples were processed for bacterial culture and analyzed for the presence of ESBL-producing E. coli. The prevalence of ESBL-producing E. coli among isolated E. coli was the highest in wastewater samples (91%) followed by human BSIs (49%), poultry (38.6%), and fecal carriage isolates from healthy pregnant females (15%). A statistically significant association was seen in the prevalence of multidrug resistance among ESBL producers (52%) and nonproducers (26%). ESBL-producing E. coli was detected in all wastewater samples tested except for the upstream river. The findings of the study showed a high prevalence of ESBL-producing E. coli in samples from all three sectors and provided baseline data based upon which strategies for the safe disposal of communal and hospital waste, integrated AMR surveillance, and control strategies could be planned and implemented.